Analysis of Indonesia Inequality Income Distribution - ., Fakhruddin; Wirda. Z, Raudhatil; Ilhamsyah Siregar, Muhammad; ., Fitriyani (KnE Social Sciences, 2020)
The relationship between income distribution inequality and inflation is widely discussed in economics. The different concepts of macroeconomic management in various countries have different implications for each country. This paper aims to examine the relationship between inequality in income distribution and inflation. Panel ARDL with semi-annual data from 33 provinces in Indonesia for the period of 2012-2018 is used in this model. The results show that changes in poverty and economic growth are not statistically significant in affecting the changes of income disparity in short run. Inflation is too low, thus it is less effective at encouraging income inequality in Indonesia. In addition, in the long run, inflation does not affect the inequality of income distribution, it is assumed that the benefits of inflation are concentrated in groups of people with high-income levels. Moreover, economic growth has a negative impact on income inequality and poverty that eventually will aggravate the imbalance in income distribution. Therefore, its is recommended for Indonesia’s economy to be directed at increasing inflation to reach the ideal level in order to be able to reduce the imbalance in income distribution. Keywords: Inequality, inflation, poverty, growth, Panel ARDL